Quantum chemical study of the enzymatic repair of T(6-4)C/C(6-4)T UV-photolesions by DNA photolyases - Faraji, Shirin; Wirz, Lukas; Dreuw, Andreas (ChemPhysChem, 2013)
Several strategies have evolved to repair one of the abundant UV radiation-induced damages caused to DNA, namely the mutagenic pyrimidine (6-4) pyrimidone photolesions. DNA (6-4)-photolyases are enzymes repairing these lesions by a photoinitiated electron transfer. An important aspect of a possible repair mechanism is its generality and transferability to different (6-4) lesions. Therefore, previously suggested mechanisms for the repair of the T(6-4)T lesion are here transferred to the T(6-4)C and C(6-4)T lesions and investigated theoretically using quantum chemical methods. Despite the different functional groups of the pyrimidine bases involved, a general valid molecular mechanism was identified, in which the initial step is an electron transfer coupled to a proton transfer from the protonated HIS365 to the N3′ nitrogen of the 3′ pyrimidine, followed by an intramolecular OH/NH2 transfer in one concerted step, which does not require an oxetane/azetidine or isolated water/ammonia intermediate.